Attachment Style and Social Skills of Children: The Function of Mediator Emotional Intelligence - Elham Ghorbanian; Hadi Mohammadloo; Mojtaba Habibi Asgarabad; Fatemeh Hasanabadi (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Many research indicated that children residential centers have the high possibility to diagnose with psychological disorders. Therefore, this study aims to predict social skill based on their attachment style and emotional intelligence undertaken to examine the role of intervention among children residential centers of state welfare organization. Materials and Methods: This research is a descriptive study. The 400 (240 boys & 160 girls) children residential centers were chosen through cluster sampling method of Tehran city. The survey questionnaire instruments were; social skills, emotional intelligence and attachment style. The data obtained from the structural equation modeling (SEM) were analyzed by using the LISERAL software. Results: Results show that attachment style directly & indirectly lead to social skill through the mediation variable of emotional intelligence. Between endogenous latent variable and the indicator of attachment style, the path coefficients were respectively 0.60 & 0.32, between endogenous latent 0.41, 0.45 & 0.94, and between the latent variable of indigenous social sill and the indicator the path coefficients were sportively 0.35, 0.50, 0.90 & 0.85. It can be said that and all the causal paths were significant. Conclusion: Considering the importance and necessity of children social skills and its effects on children's life, recognizing environmental factors such as attachment style and individual factors such as emotional intelligence can finally lead to a deeper recognition of factors affecting the transformation of children's social skills in order to present suitable methods.